2017
DOI: 10.1111/jhn.12500
|View full text |Cite
|
Sign up to set email alerts
|

Lunch‐time food source is associated with school hour and school day diet quality among Canadian children

Abstract: Background: There is limited research on the dietary behaviours of Canadian children at school, including where students obtain food from during school hours or whether lunch-time food source influences diet quality. Methods: Nationally representative cross-sectional data from 24-h dietary recalls were analysed from the 2004 Canadian Community Health Survey (n = 4589). Dietary outcomes included school hour and school day dietary intakes and School Healthy Eating Index (S-HEI) scores. Survey-weighted covariate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 45 publications
2
22
0
3
Order By: Relevance
“…Many of the interviews have mentioned the consumption of home packed lunches, and studies of school lunch habits amongst Norwegian adolescents have previously detailed the importance and predominance of the home packed lunch in Norwegian culture [ 37 , 38 ], with over 60% of young Norwegians reporting a packed lunch for consumption at school, a proportion similar to the results we present here. This figure is also consistent with global reports examining school lunch eating practises [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many of the interviews have mentioned the consumption of home packed lunches, and studies of school lunch habits amongst Norwegian adolescents have previously detailed the importance and predominance of the home packed lunch in Norwegian culture [ 37 , 38 ], with over 60% of young Norwegians reporting a packed lunch for consumption at school, a proportion similar to the results we present here. This figure is also consistent with global reports examining school lunch eating practises [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…The focus group interviews together with the quantitative data support the notion of healthy eaters avoiding the school canteen, opting instead for a home packed lunch. This view is further supported by previous reports that home prepared lunches help contribute to a healthy dietary pattern [ 39 , 62 , 63 ]. Furthermore, it has been reported that students consuming a lunch from home have significantly lower odds of consuming off-campus food during the school week [ 41 ], which further concurs with the results presented here.…”
Section: Discussionsupporting
confidence: 81%
“…Lunches prepared at home are generally considered the most nutritious option, relative to meals purchased from fast food, restaurants, and convenience store outlets (24,23). In Canadian secondary school students, those who bring a home-packed lunch report better total dietary quality, and consume fewer SSBs (25) and more fruit, vegetable (26), and whole grain servings, compared to their peers who purchase lunch from school or off campus (24,27). For purchased lunches, most studies support the school cafeteria food as the healthier alternative to food purchased at fast food outlets or other restaurant and retail options.…”
Section: Introductionmentioning
confidence: 99%
“…Students who eat lunch or snacks purchased at fast food outlets or restaurants report higher consumption of SSBs (25,26,28) and fried foods, and have greater sodium, sugar, and total caloric intakes than their peers who eat lunch prepared at home or by the school cafeteria (23,24,28). However, some evidence suggests school obtained lunches are generally equivalent to food purchased off-school property (24,27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation